Dust Continuum Radiation Maps from MHD Simulations of Accretion-ejection Systems around Single and Binary Stars - Somayeh Sheikhnezami; Christian Fendt; Sareh Ataiee (The Astrophysical Journal)
We study the launching of magnetized jets from a resistive circumstellar disk within a binary system, employing a unique combination of 3D MHD jet launching simulations (PLUTO code) and post-processed 3D radiative transfer modeling (RADMC-3D code). Our findings reveal a well-defined jet originating from the inner region of the disk, extending to a larger disk area. While the model attains steady states for a single star, a binary system leads to the emergence of tidal effects such as the formation of “spiral arms” in the disk and inside the jet. Here, we have consistently implemented a time-dependent Roche potential for the gravity of the binary. As a major step forward, we further present the first 3D radiation maps of the dust continuum for the disk-jet structure. In principle, this allows us to compare MHD simulation results to observed disk-outflow features. We, therefore, present convolved images of the dust continuum emission, employing exemplary point spread functions of the MIRI instrument (5 μ m band) and the Atacama Large Millimeter/submillimeter Array (320 μ m band). In these bands, we identify distinguishable features of the disk-jet structure, such as “spiral arms,” which we have also seen in the MHD dynamics. For gas density increased by an order of magnitude, the disk becomes optically thick at 5 μ m, but remains bright at 320 μ m. At this wavelength, 320 μ m, enhanced structural features in the disk and the base of the wind become more pronounced and are well resolved in the convolved image.